HEALTH EDUCATION PRACTICES IN THE TRAINING OF NURSING UNDERGRADUATES - Francisco Gilberto Fernandes Pereira; Joselany Áfio Caetano; Juliana Faheina Moreira; Márcia Barroso Camilo de Ataíde (Universidade Federal do Paraná, 2015)
The aim of this study was to understand the importance of health education practices in the training of nursing undergraduate students, through a qualitative descriptive study, conducted between September and October 2014 with fifty nursing undergraduates. Data were collected by means of semi-structured interviews; the statements were organized and analyzed according to the Collective Subject Discourse. Ethical standards were applied by means of opinion 889.504. Three synthetic discourses emerged, anchored on the following core ideas: concept of health education; importance of educational practices in academic education; and, difficulties in performing educational activities. It can be noted that there are similarities between the biomedical model and the implementation of educational activities; however, these are evidenced as an important professional building tool. Health education occupies a prominent position in the training of nursing students; however, it is necessary to rediscuss its concept.